Assessment and Treatment of Alcohol Withdrawal Syndrome - Ha Yeong Choi; Jeong Seock Seo; Sang Kyu Lee (The Korean Journal of Gastroenterology, 2020)
Alcohol withdrawal syndrome (AWS) is the most common and well-known condition occurring after intentional or unintentional cessation or decreasing heavy drinking. Approximately 5-10% of these people are suffering from serious medical and psychiatric problems, withdrawal seizures, perceptual disturbances, and delirium tremens. Despite acute medical conditions with the high mortality of severe AWS, proper management could decrease the severity and mortality of AWS. The Clinical Institute withdrawal assessment for alcohol-revised version is a valid, reliable, and sensitive instrument for assessing the clinical course and the treatment monitoring of alcohol withdrawal. Benzodiazepine is the pharmacotherapy of choice for alcohol withdrawal. Diazepam or lorazepam treatment is best initiated early in the course of alcohol withdrawal to prevent progression to more severe withdrawal. There are three strategies for the pharmacotherapy of AWS. After the treatment of AWS, most patients should be managed or treated by the continuing care, including the psychosocial treatments, community-based management, and programs for preventing recurrence of AWS.